2004
DOI: 10.1097/01.hjr.0000116825.84388.eb
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of maximal exercise performance in chronic heart failure

Abstract: Muscle strength and muscle endurance, combined with quadriceps muscle area are the main predictors of maximal exercise performance in patients with CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Nearly 60% of the variance of maximal workload is explained in the model that describes maximal workload as dependent variable of upper leg muscle function and quadriceps muscle area before intervention (multiple regression analysis) [12]. The same regression analysis after intervention showed that this model (Fig.…”
Section: Correlations and Modelmentioning
confidence: 86%
See 2 more Smart Citations
“…Nearly 60% of the variance of maximal workload is explained in the model that describes maximal workload as dependent variable of upper leg muscle function and quadriceps muscle area before intervention (multiple regression analysis) [12]. The same regression analysis after intervention showed that this model (Fig.…”
Section: Correlations and Modelmentioning
confidence: 86%
“…For statistical analysis, we constructed a new variable that represents the combination of skeletal muscle strength and endurance of the upper leg: upper leg muscle function (ULMF) [12]. ULMF is computed from the sum of total extension peak torque (TEPT), total flexion peak torque (TFPT), total extension total work (TETW), and total flexion total work (TFTW) divided by 4: (TEPT+TFPT+ TETW+TFTW)/4.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quadriceps mass and strength are related to maximal exercise capacity in HF [19]. Moreover, changes in muscle performance with exercise training have been demonstrated to be related to changes in physical function [20] and quality of life [21].…”
mentioning
confidence: 99%
“…1,2) Several studies have reported a strong increase of sympathetic activity, the onset of peripheral vascular remodeling, and skeletal muscle metabolic alterations in response to exercise. [3][4][5][6][7] Histochemical analyses have demonstrated extensive mitochondrial damage resulting in depressed activity of the oxidative enzymes. [8][9][10] An important contributor to the decondition in CHF is physical inactivity and, since exercise training has been shown to improve functional capacity, quality of life as well as muscle strength should be considered as an integral part of the therapy in such patients.…”
mentioning
confidence: 99%